2005
DOI: 10.1021/nl050702s
|View full text |Cite
|
Sign up to set email alerts
|

Interface Geometry and Molecular Junction Conductance:  Geometric Fluctuation and Stochastic Switching

Abstract: Metal/molecule/metal transport junctions can transport charge in the elastic scattering (Landauer) regime if the injection gap is large and the molecule is relatively short. Stochastic switching and broad conduction peak distributions have been observed in such junctions. We examine the effect of altering interface geometry on transport, using density functional calculations. For most structures, variations in conductance of order 0-300% are found, but when an atomic wire of Au binds to the molecule, symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
240
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(256 citation statements)
references
References 102 publications
13
240
3
Order By: Relevance
“…During the formation of a Au-S covalent bond, multiple bonding scenarios exist depending on the location of the H atom, which could lead to drastic changes in the rupture force 44,52 , and a possibility of forming weaker coordinate bonds between the protonated SH groups and gold surfaces 53 . Recently, a comprehensive investigation on the elongation process of molecular junctions formed by octanedithiol molecule and Au electrodes indicated that the bonds that are easiest to break are the coordinated Au-linker contacts (B0.6 nN), which are smaller than the covalent thiolate-gold junctions (from B1.5 to B2.2 nN) 52 .…”
Section: Resultsmentioning
confidence: 99%
“…During the formation of a Au-S covalent bond, multiple bonding scenarios exist depending on the location of the H atom, which could lead to drastic changes in the rupture force 44,52 , and a possibility of forming weaker coordinate bonds between the protonated SH groups and gold surfaces 53 . Recently, a comprehensive investigation on the elongation process of molecular junctions formed by octanedithiol molecule and Au electrodes indicated that the bonds that are easiest to break are the coordinated Au-linker contacts (B0.6 nN), which are smaller than the covalent thiolate-gold junctions (from B1.5 to B2.2 nN) 52 .…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] A thiol group is most commonly used to build a strong chemical link between the single molecules and the Au electrodes in molecular junctions. The conductance of such single-molecule junctions is typically several orders of magnitude smaller than G 0 =2e 2 / h ͑the conduc-tance quantum͒.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these comparisons are complicated by substantial variability in the measured values for the same molecule and signficant uncertainty about the atomic scale structure of the junction near the single molecule link [3]. Calculations are typically performed for relatively idealized junction structures and the conductance can be sensitive to the local geometry for widely used thiol linkages [16,17,18].…”
Section: Introductionmentioning
confidence: 99%